Design of novel Surfactant Modified Carbon Nanotube PasteElectrochemical Sensor for the Sensitive Investigation of Tyrosineas a Pharmaceutical Drug - Nagarajappa Hareesha; Jamballi Gangadharappa Gowda Manjunatha; Chenthattil Raril; Girish Tigari (Tabriz University of Medical Sciences, 2019)
Purpose: The novel sodium dodecyl sulfate modified carbon nanotube paste electrode (SDS/CNTPE) was used as a sensitive sensor for the electrochemical investigation of L-tyrosine (TY).Methods: The electrochemical analysis of TY was displayed through cyclic voltammetry (CV)and differential pulse voltammetry (DPV). The surface morphology of SDS/CNTPE and barecarbon nanotube past electrode (BCNTPE) was reviewed trough field emission scanning electronmicroscopy (FESEM).Results: The functioning SDS/CNTPE shows a voltammetric response with superior sensitivitytowards TY. This study was conducted using a phosphate buffer solution having neutral pH(pH=7.0). The correlation between the oxidation peak current of TY and concentration of TYwas achieved linearly in CV method, in the range 2.0×10-6 to 5 ×10-5 M with the detection limit729 nM and limit of quantification 2.43 μM. The investigated voltammetric study at SDS/CNTPEwas also adopted in the examination of TY concentration in a pharmaceutical medicine as a realsample with the recovery of 97% to 98%.Conclusion: The modified electrode demonstrates optimum sensitivity, constancy, reproducibility,and repeatability during the electrocatalytic activity of TY.